Notes on decolonial thought and sustainability - Suguimoto, Djmes Yoshilazu de Lima; Fernandes, Fernanda Bellucci; Maciel, Josemar Campos (Multitemas, 2017)
Nowadays there is a substantial group of authors that favour the thought about the planet in unorthodox ways, since it is not formed in a Cartesian manner, not only quantified. In the present study scientists who work with the decolonial approach are studied, in other words, modifying the imposed view by groups and economic system in a multicultural society, thinking about the transformation of the planet favoring those who are invisible. All the theorists in this work converge to a fair society, where the respect to different cultures is synonym of a decolonial world being intimately related to the local development theory. This work has as goal to show the criticism these researchers make to the current system, which is aggressive and dissolves many groups that does not accept the modus operandi stablished.